Implementation of Total Quality Management (TQM) in the Implementation of Education Quality Control in Information Engineering Study Program - Dian Rosinawati; Ifah Khadijah; Waska Warta (UIN Sunan Gunung Djati Bandung, 2021)
The main key to quality education management is how to carry out good and quality education to give birth to a generation of people who have potential, abilities, talents that grow and develop in all areas of life so that they are able to compete globally. For the implementation of quality education (quality), quality organizational management is also needed, one of which is by implementing Total Quality Management. Efforts to standardize quality and guarantee the implementation of higher education must meet quality standards in an effort to maintain and improve the quality of education nationally. In general, the definition of quality assurance in higher education is: The process of establishing and fulfilling education quality standards consistently and continuously so that customers get satisfaction. The process to ensure that the quality of graduates is in accordance with the specified/promised competencies so that quality can be consistently maintained and continuously improved.